2017
DOI: 10.15353/cfs-rcea.v4i1.191
|View full text |Cite
|
Sign up to set email alerts
|

Organic vs. Local: Comparing individualist and collectivist motivations for “ethical” food consumption

Abstract: We extend prior research on "ethical" food consumption by examining how motivations can vary across demographic groups and across types of ethical foods simultaneously. Based on a survey of food shoppers in Toronto, we find that parents with children under the age of 5 are most likely to report intention to purchase organic foods and to be primarily motivated by health and taste concerns. In contrast, intention to purchase local food is motivated by collectivist concerns-the environment and supporting the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The data showed that egocentric benefits outweigh altruistic benefits, as perceived by consumers. Empirical evidence suggests that people make food choices by taking these two types of perceived benefits into account, and recent studies tend to approach food labels with an emphasis on ethical and social responsibility considerations (Baumann et al. , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The data showed that egocentric benefits outweigh altruistic benefits, as perceived by consumers. Empirical evidence suggests that people make food choices by taking these two types of perceived benefits into account, and recent studies tend to approach food labels with an emphasis on ethical and social responsibility considerations (Baumann et al. , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This result defines how the connection between organic and local is true both in more limited geographical contexts, such as the one explored in Massaglia et al [16] but also at the European level. In fact, this local/organic relationship has been extensively studied in several countries and has been found to be decisive in the choice of certain food products, such as fruit and vegetables specifically [4,5,8,21,34,35]. For example, in a study conducted in Northern Europe, the same product opinions emerged that motivated organic and local food consumers [1].…”
Section: Discussionmentioning
confidence: 99%
“…Local fruits and vegetables, instead, are described by many definitions. These definitions depend on consumer perception, cultural heritage, and existing legislation/regulations but always refer to a restricted growing area located near the selling area and connected to environmentally friendly topics [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Ambitious local food initiatives, spearheaded by advocates for environmental responsibility, community economic development, small farmers and food insecure populations, frequently take for granted the idea that vibrant local food systems carry significant environmental benefits. And consumers tend to buy into the narrative of green, socially beneficial local food (Cranfield et al, 2012; Megicks et al, 2012; Meas et al, 2015; Baumann et al, 2017), even seeing participation in the locavore movement as a kind of ‘small-p politics’ that affords apolitical people a way to quietly create spaces for social change (Kennedy et al, 2017). But the claims of local food advocates and the beliefs of consumers belie a surprising fact: profound disagreement exists over what the relationship between robust local food systems and positive environmental outcomes might actually be (Born and Purcell, 2006; Lilico, 2008; Rankin, 2009; McCaffrey and Kurland, 2015).…”
Section: Discussionmentioning
confidence: 99%